A Comparative Study on the Calculating of Thickness and Height at T-Shaped Branch for KS D 3595 Stainless Steel Pipe using the Results both the Finite Element Method and the Experiment - Nam, Jun-Seok; Ryou, Hong-Sun (Fire Science and Engineering, 2020)
Stainless steel pipe for general piping specified under the KS D 3595 standard is used as a substitute for carbon steel pipe in places where corrosion of coastal regions is a concern because there is little risk of corrosion. In order to install the branch pipe from the main pipe, the pipe is punched into the elliptical shape and the cone-shaped plug is pulled out of the main pipe to form a T-Shaped branch portion. However, there is a problem that is damaged when welding the pipe to the branch, but it is insufficient to understand the behavior of the material and the principle of damage due to plastic deformation when forming the branch. Hence, in this study, material behavior and stress were analyzed through finite element analysis. The diameter of the KS D 3595 stainless steel main was varied from 75 mm to 100 mm and the diameter of the branch pipe was varied from 25 mm to 80 mm. So, a total of eighteen cases were analyzed. The obtained results indicate that the maximum residual stress occurs in the central portion of the pipe along the longitudinal direction of the branch, and the residual stress increases as the size of the branch processing portion increases. Furthermore, in this study the minimum cutting height required for compatibility with the minimum thickness of the branching portion is reported.